Media Pembelajaran Teka Teki Silang Pada Mata Pelajaran IPS Kelas V Di MI Islamiyah 1 Surowono Badas – Kediri - Sri Putrianingsih (POJOK GURU: Jurnal Keguruan dan Ilmu Pendidikan, 2024)
Learning media is an inseparable part of learning activities in schools. Learning media is very important for educators to use in the KBM (Teaching and Learning Activities) process. There are various types of learning media that can be applied in the teaching and learning process, one of the learning media is Crossword Puzzles (TTS). The cooperative learning model with the help of crossword puzzles (TTS) in social studies subjects can make students more active and improve their social life. The Cooperative learning model with the help of Crossword Puzzle (TTS) media can increase the activity of class 5-B students at MI Islamiyah 1 Surowono, namely in the results of the LKPD (Student Worksheet) they work on, they discuss each other with group members and are enthusiastic in doing it.